Masculinities in Literature of the American West - Cooper, Lydia R. author. aut Link
XIII, 197 p.
Keywords: The Western genre provides the most widely recognized, iconic images of masculinity in the United States - gun-slinging, laconic white male heroes who emphasize individualism, violence, and an idiosyncratic form of justice. This idealized masculinity has been fused with ideas of national identity and character. Masculinities in Literature of the American West examines how contemporary literary Westerns push back against the coded image of the Western hero, exposing pervasive anxieties about what it means to "act like a man." Contemporary Westerns critique assumptions about innate connections between power, masculinity, and "American" character that influence public rhetoric even in the late 20th and early 21st centuries. These novels struggle with the monumental challenge of all Westerns: the challenge of being human in a place where "being a man" is so strictly coded, so unachievable, so complicit in atrocity, and so desirable that it is worth dying for, worth killing for, or perhaps worth nothing at all.